Inducing Disbelief in Free Will Alters Brain Correlates of Preconscious Motor Preparation - Rigoni, Davide; Kühn, Simone; Sartori, Giuseppe; Brass, Marcel (Psychological Science, 2011)
The feeling of being in control of one’s own actions is a strong subjective experience. However, discoveries in psychology and neuroscience challenge the validity of this experience and suggest that free will is just an illusion. This raises a question: What would happen if people started to disbelieve in free will? Previous research has shown that low control beliefs affect performance and motivation. Recently, it has been shown that undermining free-will beliefs influences social behavior. In the study reported here, we investigated whether undermining beliefs in free will affects brain correlates of voluntary motor preparation. Our results showed that the readiness potential was reduced in individuals induced to disbelieve in free will. This effect was evident more than 1 s before participants consciously decided to move, a finding that suggests that the manipulation influenced intentional actions at preconscious stages. Our findings indicate that abstract belief systems might have a much more fundamental effect than previously thought.